GOOD HOOK AS ATTENTION GRABBER IN EFL STUDENT’S ESSAYS: A REVIEW FROM READER’S PERSPECTIVE - Zia Hisni Mubarak; Gaguk Rudianto (BASIS (Bahasa dan Sastra Inggris), 2020)
This article provides a review from the reader's point of view of essays’ hook written by EFL students in Putera Batam University. The purpose of this study is to provide an overview of the effectiveness of the opening sentence which is able to attract readers to read the entire essay or perhaps ignore it altogether. By acting as a reader, the researcher then provides a review of the opening sentence in the introductory paragraph. This research uses descriptive research method. The data is taken from the student's writing task. The data are then grouped based on how to make a good hook and analyzed based on how to write a good hook. The researchers act as the reader and uses their point of view to judge an interesting hook. The results obtained from this study are 23 data hooks using questions, 17 data hooks with interesting observations, 11 data hooks had unique scenarios, 4 data hooks using famous quotes and 3 data with statistics. Furthermore, the remaining 6 data were identified not to write hooks using these five methods. From this review, it can be concluded that writing hooks is not as easy as it seems, because to attract readers' interest the writer should be able to see the hook from the reader's point of view.